Diagnostic challenges and laparoscopic management of mitotically active cellular fibroma of the ovary: a case report and literature review - Tian, Shuxu; Hao, Juan; He, Yulu; Liu, Xuan; Song, Huangbei; Geng, Chenchen (Frontiers in Oncology, 2025)
Mitotically active cellular fibroma (MACF) is a rare ovarian neoplasm characterized by mild to moderate cytological atypia and increased mitotic activity, often presenting diagnostic challenges due to its overlap with ovarian fibrosarcoma. Although MACF has low malignant potential and generally confers a favorable prognosis, accurate diagnosis is essential to avoid overtreatment and to guide appropriate management. We retrospectively analyzed a 33-year-old woman with a 5cm left ovarian mass showing abundant vascularity on ultrasonography. Pathological examination revealed a cellular fibroma with moderate atypia, a high mitotic rate (15/10 High-Power Fields [HPF]), and a Ki-67 index of 60%, creating diagnostic ambiguity with fibrosarcoma. Following multidisciplinary review and adherence to World Health Organization (WHO) criteria, a diagnosis of MACF was confirmed. The patient underwent laparoscopic unilateral salpingo-oophorectomy, with en bloc removal of the tumor. Her postoperative course was uneventful, and no recurrence was observed after over two years. This case underscores that high proliferative indices alone are insufficient for a fibrosarcoma diagnosis and highlights the safety and efficacy of minimally invasive, fertility-sparing surgery for MACF in young patients.